2023
DOI: 10.1002/aic.18011
|View full text |Cite
|
Sign up to set email alerts
|

Surface phase transformation of ZrO2 in VOx/ZrO2 catalysts for boosting propane nonoxidative dehydrogenation

Abstract: The nanocatalysts of VOx deposited on ZrO2 supports with single monoclinic (ZrO2‐M), tetragonal (ZrO2‐T), and binary monoclinic‐tetragonal (ZrO2‐MT) phase were synthesized. VOx/ZrO2‐MT catalysts exhibit better performance during propane nonoxidative dehydrogenation than VOx/ZrO2‐M and VOx/ZrO2‐T catalysts. Among VOx/ZrO2‐MT catalysts, the conversion and deactivation rate constant of VOx/ZrO2‐M31T69 catalyst is 35.2% and 0.22 h−1, respectively. The promoting role of ZrO2‐MT is revealed by experiments and theore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Previous studies suggested that the ratio of isolated to polymerized VO X species decreases with the increase of E g values, and the values at 3.0−3.6 eV are attributed to low-polymerized VO X species. 44,49,50 Thus, isolated VO 4 species are dominant in 1V/SSZ possessing the highest E g value (3.79 eV), and with the increase of vanadium loading to 5 wt %, low-polymerized VO X species start to be formed and become prominent. Further increasing vanadium loading to 12 wt % contributes to an obvious decrease of E g values to 2.71 eV and an significant increase of CVB number (calculated based on the empirical equation CVB = −3.95E g + 14.03 established by Wachs and co-workers 51 ) to 3.33 (Table S1), potentially suggesting the formation of numerous highpolymerized VO 5 or VO 6 species for the V 2 O 5 -containing 12V/SSZ catalyst.…”
Section: Uv−vis Spectroscopymentioning
confidence: 99%
“…Previous studies suggested that the ratio of isolated to polymerized VO X species decreases with the increase of E g values, and the values at 3.0−3.6 eV are attributed to low-polymerized VO X species. 44,49,50 Thus, isolated VO 4 species are dominant in 1V/SSZ possessing the highest E g value (3.79 eV), and with the increase of vanadium loading to 5 wt %, low-polymerized VO X species start to be formed and become prominent. Further increasing vanadium loading to 12 wt % contributes to an obvious decrease of E g values to 2.71 eV and an significant increase of CVB number (calculated based on the empirical equation CVB = −3.95E g + 14.03 established by Wachs and co-workers 51 ) to 3.33 (Table S1), potentially suggesting the formation of numerous highpolymerized VO 5 or VO 6 species for the V 2 O 5 -containing 12V/SSZ catalyst.…”
Section: Uv−vis Spectroscopymentioning
confidence: 99%
“…Against this background, various materials have been developed. The most promising candidates are catalysts with supported GaO x , VO x , or CoO x species. Considering the cost and environmental friendliness of zinc, ZnO x -based catalysts are of particular interest.…”
Section: Introductionmentioning
confidence: 99%